2005
DOI: 10.4161/cbt.4.7.1802
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of the human hedgehog interacting protein (HHIP) gene in pancreatic neoplasms

Abstract: Hedgehog pathway overactivity has been implicated in the development of a variety of human cancers. The Human Hedgehog interacting protein (HHIP), a negative regulator of hedgehog signaling, has been shown to be underexpressed in pancreatic cancers. In this study we determined if the HHIP gene is a target for genetic and epigenetic alterations. While no mutations of HHIP were identified, we found complete methylation of the HHIP promoter CpG island in three pancreatic cancer cell lines, and partial hypermethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 33 publications
5
62
0
Order By: Relevance
“…Because CpG islands have been located around the transcription start site of the negative regulators of Hh signaling PTCH1 and HHIP, they represent valid candidates for hypermethylation-associated transcriptionally silencing in human cancers. [21][22][23][24] Using bisulfite sequencing, we found no methylation of the promoter-associated CpG island of the PTCH1 gene in normal and malignant liver cells (data not shown), which is consistent with the high PTCH1 expression found (Fig. 1A).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Because CpG islands have been located around the transcription start site of the negative regulators of Hh signaling PTCH1 and HHIP, they represent valid candidates for hypermethylation-associated transcriptionally silencing in human cancers. [21][22][23][24] Using bisulfite sequencing, we found no methylation of the promoter-associated CpG island of the PTCH1 gene in normal and malignant liver cells (data not shown), which is consistent with the high PTCH1 expression found (Fig. 1A).…”
Section: Resultssupporting
confidence: 75%
“…13 An alternative mechanism causing activation of Hh signaling in pediatric liver tumors comes from our data on the methylation status of the HHIP gene, which clearly showed that HHIP expression is strongly reduced through CpG island hypermethylation in a subset of cases. Several lines of evidence have already indicated that HHIP expression could be transcriptionally silenced by CpG island hypermethylation, as shown for pancreatic, 21 gastrointestinal cancers, 34 and just recently HCC. 35 The absence or significant decrease of HHIP mRNA levels found in lung and liver cancers 15,36 additionally suggest a broader role of this epigenetic alteration in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…NCI-H929 cells coexpressed INDIAN HEDGEHOG (IHH), PTCH1, SMO, and GLI1. In addition, all of the MM cell lines lacked expression of HHIP, a secreted Hh ligand antagonist that is epigenetically silenced in pancreatic cancer (26). This expression pattern resembles that of other cancers in which Hh signaling may play an important role (14,17).…”
Section: Resultsmentioning
confidence: 99%
“…IHH is significantly upregulated in primary pancreatic cancer (56). CpG hyper-methylation of HHIP1 promoter was detected in 13 out of 17 pancreatic cancer cell lines, and in 35 out of 75 primary pancreatic cancer (50).…”
Section: Hedgehog Signaling In Gastrointestinal Cancermentioning
confidence: 99%
“…On the other hand, HHIP1 is downregulated in a variety of tumors, such as gastric cancer, pancreatic cancer, colorectal cancer, and lung cancer (49). HHIP1 down-regulation in pancreatic cancer is due to epigenetic CpG hypermethylation (50).…”
Section: Oncogenic Hedgehog Signaling Activationmentioning
confidence: 99%